1985
DOI: 10.1128/aem.49.1.205-210.1985
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Fermentation with Trichoderma reesei for Cellulase Production

Abstract: Cellulase yields of 250 to 430 IU/g of cellulose were recorded in a new approach to solid-state fermentation of wheat straw with Trichoderma reesei QMY-1. This is an increase of ca. 72% compared with the yields (160 to 250 IU/g of cellulose) in liquid-state fermentation reported in the literature. High cellulase activity (16 to 17 IU/ml) per unit volume of enzyme broth and high yields of cellulases were attributed to the growth of T. reesei on a hemicellulose fraction during its first phase and then on a cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1
7

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(53 citation statements)
references
References 16 publications
(16 reference statements)
1
44
1
7
Order By: Relevance
“…7,22 To assess the overall activity of these enzymes in all fungal cultures and to generate a better grape biomass degradation method, process optimization was carried out. Generally, about 1:1 cellulase: -glucosidase activities have been reported to yield higher outputs under SSF conditions 10,31 but this varies across the species and type of substrates. wileyonlinelibrary.com/jctb The fitted ANOVA model was generated using the data provided in Fig.…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…7,22 To assess the overall activity of these enzymes in all fungal cultures and to generate a better grape biomass degradation method, process optimization was carried out. Generally, about 1:1 cellulase: -glucosidase activities have been reported to yield higher outputs under SSF conditions 10,31 but this varies across the species and type of substrates. wileyonlinelibrary.com/jctb The fitted ANOVA model was generated using the data provided in Fig.…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…generation (Chahal 1985;Nigam and Singh 1994). Cruz and Park (1982), Kotwal et al (1997), Li et al (2001) and Wang et al (2004) had reported alpha-galactosidase production in SSF.…”
mentioning
confidence: 99%
“…Wheat straw is the second most abundant lignocellulosic raw material in the world after rice (Sarkar et al 2012). It was extensively used in preparation of cellulolytic or hemicellulolytic enzymes by fungal fermentation or bio-ethanol production based on its cellulose (35-45%) and hemicellulose (20-30%) contents (Chahal 1985;Sarkar et al 2012). In this study, E. parvum 4-14 displayed an excellent ability of producing (hemi-)cellulase enzymes using wheat straw and wheat bran as substrate.…”
Section: Discussionmentioning
confidence: 93%
“…Solid-state fermentation, as an effective and low-cost approach, was widely used in preparation of lignocellulolytic enzymes from fungi (Chahal 1985;Latifian et al 2007;El-Shishtawy et al 2015). Wheat straw is the second most abundant lignocellulosic raw material in the world after rice (Sarkar et al 2012).…”
Section: Discussionmentioning
confidence: 99%